Sport Education Model (SEM): Its Effect on Physical Self-Concept (PSC) and Invasion Game Learning Outcomes in Elementary Schools - Suherman Slamet; Lukmannul Haqim Lubay; Wildan Alfia Nugroho; Wulandari Putri; Mesa Rahmi Stephani (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of the sport education model on physical self-concept and the learning outcomes of invasion game activities in physical education learning. This study used the PSCQ-C questionnaire to measure PSC and TGMD-2 to measure student learning outcomes. This research used experimental method. The research population were upper class students at SDN 178 Gegerkalong KPAD Bandung City, involving 42 students as samples. Based on the results of statistical test data research, the significance value of SEM on PSC pre-test and post-test was Sig. 0.000 0.05, indicating there was a significant difference. While the significance value of SEM on learning outcomes was Sig. 0.000 0.05. These results indicate that there was a significant difference in mean scores between the results of pre-test and post-test of PSC and learning outcomes of the student in invasion game.